APLIKASI RAPORT ONLINE BERBASIS WEB MENGGUNAKAN FRAMEWORK CODEIGNITER - Dheni Apriantsani Budiman; Decky Maulana Nugraha (STMIK Mardira Indonesia, Bandung, 2019)
Online Report Card Application is a Web-based application that is used to facilitate the delivery of student learning outcomes, thus helping speed and quality in delivering information. The problems that occur in the processing of grades at SMK Angkasa 1 Margahayu at this time are that every subject teacher cannot see the report card grades before being given to students, it is feared an error will arise by the homeroom teacher in filling out report cards and also parents of students who are unable to be present when submitting report cards will not be able to see the results of their children's learning and data storage that has not been organized. This study aims to build a value application that makes it easier to check, record and report computerized student grade data. Also with web-based data information can be accessed at any time. The research methodology used is descriptive method. The system development method used is to use the OOSE Method, the Programming Language used is PHP, widely used to program dynamic websites. The framework used is Codeigniter is an open source application in the form of a PHP framework with the MVC model (Model, View, Controller). This application uses a multiuser consisting of admin, teacher, principal, guardian and guardian of students. in the login section when opening an application so that the security of the program is there. This application works to enter and store data reports on grades and absences so that it is easier to find out information on values. This research has produced an online report card application to process values that help the work of teachers and homeroom teachers and can facilitate users to process values so that value management can be processed effectively and efficiently, so that it can be directly accessed and information can be conveyed with well.. Key Word : Application, Smk Angkasa 1 Margahayu, Report Card, Codeigniter DOI : http://doi.org/10.5281/zenodo.3631061